PERUBAHAN PELAKSANAAN DO’A PADANG DI DESA SEBERANG PULAU BUSUK KECAMATAN INUMAN KABUPATEN KUANTAN SINGINGI - Latipa Santika; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Padang prayer is a prayer that is done once a years. Padang prayer in the village across from this rotten insland is a prayer that was once done in the field or done near the batang kuantan river by the village across from the rotten islan. Implementation of the Padang prayer which is now being done in the mosque. The purpose of the implementation of this Padang prayer is, safe in farming, safe for the village and safe in whatever happens in the village across form the rotten island. The research method used in this study is a qualitative research in order to obtain clear data and data collection techniques in the form of interviews and documentation. Based on the analysis of the Padang preyer, it can be concluded that this Padang Preyer is a prayer that has been around for a long time, since time immemorial. Our ancestour used to be, and until now this Padang Prayer is still being carried out even implementation of the Padang Prayer.Keywords: Field Prayer, change, Desatination.